The Role of Psychological Hardiness and Spiritual Health in Predict of Quality of Life in Students of Kermanshah University of Medical Sciences - Afsaneh Shahbazirad; Firoozeh Ghazanfari; Manzar Abbasi; Fereshteh Mohammadi (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Nowadays, quality of life is one of the main phenomena in health, which is affected by different factors. The aim of this study was to investigate the role of psychological hardiness and spiritual health in predicting the quality of life among students. Materials and Methods: This descriptive-correlational study was conducted on 120 students of Kermanshah University of Medical Sciences, Iran, during 2013-2014. Participants were selected by cluster sampling method. Data were collected using a demographic questionnaire, Ahvaz psychological hardiness questionnaire, spiritual health questionnaire of Paloutzian & Park and Quality of life questionnaire. Data were analyzed in SPSS 19 using Pearson's correlation test and stepwise regression analysis. Results: There was a significant positive correlation between psychological hardiness and quality of life (P < 0.05). There was a significant positive correlation between spiritual health and quality of life (P < 0.05). However, there was no significant relationship between quality of life and spiritual health in the existential dimension; while, there was a significant relationship with religious dimension (P < 0.05). Psychological hardiness and spiritual health can predict 11.3 % of the variance in quality of life. Conclusions: Considering the relationship between the variables, it is better to provide training packages about the increase of spiritual health and psychological hardiness, in order to enhance the quality of life of university students.